2020
DOI: 10.1021/acs.jafc.0c05261
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biosynthesis of Dihydromyricetin in Saccharomyces cerevisiae by Coexpression of Multiple Hydroxylases

Abstract: Dihydromyricetin (DHM) is a traditional plant-extracted flavonoid with some health benefits. This study aimed to metabolically engineer the strains for DHM bioproduction. Two strains of BK-11 and BQ-21 were integrated with flavonoid 3hydroxylase (F3H) or both F3H and flavonoid 3′-hydroxylase (F3′H). The resulting strains have expressed the enzymes of GmCPR and SlF3′5′H, and then, the promoters of INO1p and TDH1p were used to enhance further the DHM production from naringenin in Saccharomyces cerevisiae. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…4-coumarin-CoA ligase (4CL), CHS, and CHI are pivotal in synthesizing naringenin. At present, the primary way to improve the efficiency of heterologous synthesis of naringenin is to regulate the expression of critical enzymes, the activity of critical enzymes, and reaction conditions ( Ibdah et al, 2018 ; Gao et al, 2020a , b ; Li et al, 2020 ). Although the by-product produced by CHS (CTAL, p -coumarin triacetactone lactone and BYN, bis-noryangonin) was not detected in plants, the by-product produced by CHS derailment had been confirmed ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…4-coumarin-CoA ligase (4CL), CHS, and CHI are pivotal in synthesizing naringenin. At present, the primary way to improve the efficiency of heterologous synthesis of naringenin is to regulate the expression of critical enzymes, the activity of critical enzymes, and reaction conditions ( Ibdah et al, 2018 ; Gao et al, 2020a , b ; Li et al, 2020 ). Although the by-product produced by CHS (CTAL, p -coumarin triacetactone lactone and BYN, bis-noryangonin) was not detected in plants, the by-product produced by CHS derailment had been confirmed ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…DMY has been produced using metabolically engineered strains, namely Saccharomyces cerevisiae. S. cerevisiae is an excellent host to readily express cytochrome P450 enzymes, which are suitable for production of hydroxylated flavonoids without pronouncedly affecting its growth [54]. The de novo biosynthetic pathway of DMY in S. cerevisiae involves two steps: the production of precursor naringenin and the biotransformation from naringenin to DMY.…”
Section: Extraction Separation and Purificationmentioning
confidence: 99%
“…4 . Finally, in a 5 L bioreactor, a yield of 246.4 mg/L DMY was achieved with a total flavonoid content at 528.9 mg/L [54], suggestive that DMY amounted for 50% of total flavonoids comparable to 35% in A. grossedentata .…”
Section: Extraction Separation and Purificationmentioning
confidence: 99%
“…Several studies have demonstrated that boosting the supply of aromatic amino acid and malonyl-CoA precursors could effectively increase the production of flavonoids, whether in S. cerevisiae or in Y. lipolytica [ 32 , 36 , [46] , [47] , [48] , [49] ]. Overexpression of mutants of DAHP synthase ARO4 and chorismate mutase ARO7 could avoid feedback inhibition of aromatic amino acids and thereby increase the yield of flavonoid and stilbene products [ 50 ].…”
Section: Resultsmentioning
confidence: 99%